Legal Obstacles in Medical Communication - Okoński, Jan (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
This paper discusses medical communication as an issue, important from the point of view of the functioning of the health service. Attention is paid to the spheres of interpersonal and institutional communication, and selected legal obstacles in medical communication are presented, mainly in the relationship between medical personnel and the patient. The communicological aspect of the discussed issue was especially taken into account. For this purpose, the concept of communicology and the associated terminological problems have been presented. The discussed matter was analyzed through the prism of the thesis about excessive juridization of the sphere of communication.